Numerical Simulation of Stainless Steel Powder Feeding in a Coaxial Nozzle for High Powder Efficiency in Laser Direct Energy Deposition - Kumar, Hemanth; M, Manjaiah (Frontiers in Mechanical Engineering, 2022)
Direct energy deposition (DED) is an efficient manufacturing process for fabrication of complex parts and repairing worn-out turbine blades. In DED all the injected powder is not going to melt and solidify due spattering, reflection, ejection, effect of inert gas and turbulence around the melt pool. In this study, through numerical simulation effect of powder size and inert gas flow under coaxial nozzle was analyzed. The number of particles participation in melt pool by the effect of inert gas and size of powder particles were analyzed. The powder particle size was considered for the study were 50-60µm, 60-70µm, 70-80µm, 80-90µm, 90-100µm and 45-90 µm. Argon and Helium gases were used as carrier gas and shielding gas. According to gas-solid multiphase simulation, the convergence distance of the powder flow and powder participation focal point were analyzed through numerical simulation. The simulated results showed that using argon gas as a carrier gas is producing high powder efficiency compared to helium gas. The focal point is forming at 11.86 mm approximately 12mm from nozzle exit which occurred for 60-70µm particle size. The powder particle participation efficiency obtained was 64.1% using argon gas as carrier gas.